The Study of drought tolerance capacity of Ceratoides arborescens (Mongolian Journal of Agricultural Sciences, 2021)
The Ceratoides arborescens is the kind of plant that can live in drought or extremeness drought condition. In drought grassland, desertification grassland and desertification area, they have important value in economy and ecology. The Ceratoides arborescens is one of the promising drought resisting species for developing natural meadow. In the article, a study was developed on two ecotypes of Ceratoides arborescens by observing physiological and biochemical indices of them. The results could be used to evaluate the drought resistance ability, give a guide for Ceratoides arborescens introduction, and make a function on desert control and water and soil conservation, developing meadow and pasturing by planting plant of the Ceratoides arborescens. The photosynthesis and chlorophyll content were gradually decreased with the increase of drought stressed days. In the stressed period, the decrease of ecotype of Kerqin’s photosynthesis and chlorophyll were less than that of ecotype of Wu. The proline and malondialdehyde (MDA) were gradually increased with the increase of drought stressed days. In the stressed period, the increase of ecotype of Kerqin’s proline and MDA were more than that of ecotype of Wu during the stressed period, the activity of superoxide dismutase (SOD) and catalase (CAT) increased firstly, reached the climax on the sixth day after stressed, then decreased. The activity of SOD and CAT of ecotype of Kerqin were higher than that of ecotype of Wu. It is considered that two ecotypes in Ceratoides arborescens both have strong drought resistance ability, and analyzing results of main component analysis and comprehensive appraisal of all indices, the drought resistance ability of ecotype of Kerqin is stronger than ecotype of Wu.Морин тэсэг (Ceratoides arborescens)-ийн ган тэсвэрлэх чадварын судалгааМорин тэсэг нь удаан хугацааны туршид усгүй, гантай нөхцөлд амьдарч чаддаг ургамлуудын нэг юм. Тэсгийн төрлийн ургамлыг бэлчээр сайжруулахад ашиглах боломжтой бөгөөд хуурай уур амьсгалтай улиралд малын гол тэжээл болохоос гадна элсэрхэг хөрсөнд ургаж, элсний нүүдлийг зогсооход чухал нөлөөтэй. Бид энэхүү судалгаанд Морин тэсгийн Хорчин ба Улаанцав хэмээх 2 экотипийг ердийн усалгаатай нөхцөлд болон зохиомлоор гангийн стресст оруулсан нөхцөлд харьцуулан судалж гангийн стресс тэсвэрлэх чадварыг нь тогтоов.Гангийн стрессийн үргэлжлэх хугацаа уртсах тусам фотосинтезийн эрчим болон хлорофиллын агууламж хоёр экотипийн морин тэсэгт буурч байсан хэдий ч Хорчин тэсгийнх Улаанцав тэсгийнхээс 2.69% болон 0.19%-иар тус тус их байв. Гангийн стрессийн үргэлжлэх хугацаа уртсах тутам Морин тэсгийн хоёр экотипийн пролин ба малондиальдегидын агууламж нэмэгдэж байв. Супероксид дисмутаза (SOD) болон каталаза (CAT)-ийн идэвхжилт гангийн стрессийн үргэлжлэх эхний үед нэмэгдэж, дараа нь буурах зүй тогтолтой байсан бөгөөд Хорчин экотип нь Улаанцав экотипээс ганд илүү тэсвэртэй болох нь тогтоогдлоо. Түлхүүр үгс: хлорофилл, пролин,  малондиальдегид, физиологийн үзүүлэлт, ган тэсвэр